(untitled) (Sains Humanika, 2010)
Hibah (gift inter vivos) is one of the principles of Islamic transaction that are applied at Islamic Financial Institutions in Malaysia. The purpose of this article is to discuss the application of hibah in Islamic banking as well as the takaful. In the collection of data on the application of hibah at these Islamic institutions, the writer has conducted interviews with authoritative persons at the Shariah Division Bank Negara Malaysia, the Shariah Compliant Department at Etiqa Takaful Bhd and the Takaful Ikhlas Sdn. Bhd. The writer found that even though hibah is not considered as a core principle, but it is applied as a support principle in Islamic transaction activities in the institutions of Islamic Finance in Malaysia.